Library Research: Teachers’ Difficulties and Strategies in Designing Lesson Plan Based on the Merdeka Curriculum - Dahlia; Ira Maisarah (Journal of English for Specific Purposes in Indonesia, 2025)
The successful implementation of learning is dependent on the student and the teacher. Teachers play an important role in implementing the Merdeka Curriculum, so continuous professional development is essential to ensuring quality learning outcomes. Good teaching and the application of curriculum policies are supported by an efficient lesson plan. A lesson plan is an important component of teaching. Teachers must be able to create lesson plans appropriate to the material to be delivered, and teachers must also adjust to the character of their students when designing lesson plans. Some teachers still do not understand how to make lesson plans in the Merdeka Curriculum. The aim of this study was to examine teachers’ difficulties and strategies in designing lesson plans based on the Merdeka Curriculum. This study used a qualitative method. In collecting data, the authors used library research. The result stated that teachers have difficulty determining the learning approach, choosing a learning method, formulating the objective of learning based on the learning outcome, selecting the media in teaching, formulating differential material, formulating real-life context, designing lesson steps within time constraints, designing learning activities based on students’ interests, and formulating worksheets and assessments. The teachers can overcome this problem by: checking guidebooks, joining in-house training (IHT), attending the English Teacher Working Group (MGMP), using the Merdeka Mengajar platform, consulting with more seasoned colleagues, collaborating with other teachers, and adapting lesson plans.